Prevalence of Newcastle Disease Viruses in Wild and Captive Birds in Central Nigeria - Ibu, O.J.; Okoye, J.O.A.; Adulugba, E.P.; Chah, K.F.; Shoyinka, S.V.O.; Salihu, E.; Chukwuedo, A.A.; Baba, S.S. (International Journal of Poultry Science, 2009)
Newcastle disease (ND) is an acute rapidly spreading, contagious, nervous and respiratory disease of domestic and wild birds caused by the Avian Paramxyovirus 1, the Newcastle disease (ND) virus. ND is endemic in Nigeria. The reservoir status of wild and captive birds for ND virus in central Nigeria is assessed in this study. Cloacal swabs were taken from one hundred and sixty three birds caught from five Local Government Council areas of Plateau, Benue and Kaduna States in central Nigeria. A total of thirteen ND Viruses were isolated from the three States. Viz: 8 isolates from Plateau, 4 from Benue and 1 from Kaduna State. One hundred and fifty three of the birds sampled belonged to 30 avian species in 10 Orders while ten birds were unidentified. Only 7% of the species in three Orders yielded ND viruses. The 13 isolates were characterized using the Mean death time of the Minimum lethal dose (MTD/MLD); Intracerebral Pathogenicity index (ICPI) Intravenous Pathogenicity index (IVPI) and the Reverse transcriptase polymerase chain reaction (RT/PCR). The results show that 12 of the isolates were of the lento genic strain while 1 isolate belonged to the Merogenic strain. The implication of these findings on the poultry industry in the country is discussed.